La distribución de costos y beneficios de un Gran Proyecto Urbano : el caso del Barrio Parque Donado-Holmberg - Mancuello, Gabriel (2024)
This study analyzes the formulation, implementation and management of urban megaprojects. Taking the case of "Barrio Parque Donado-Holmberg" as a reference, it focuses particularly in the distributive and inclusive aspects that this type of interventions can contemplate, situated from a critical perspective.\nThe project has been developed in the city of Buenos Aires since 2009, and was the outcome of a broader historical evolution of housing problems and socio-territorial tensions. In this project, the intervention was implemented in a previously-settled area, a characteristic that differentiates it from other urban megaprojects.\nThe results of the study expose the project as a product of transitions between different interventions strategies over time, reflecting the inclusion of new agendas and the adaptation of emergent demands. Throughout its implementation, the project shifted toward a logic of urban entrepreneurialism, and despite having taken into account the needs of the previously settled community, the characteristics of its implementation and temporal evolution -with its actions and omissions- cast doubt on the inclusive and distributive aspects of this intervention.